Immunoglobulin G and Free Kappa-Chain Synthesis in Different Clones of a Hybrid Cell Line - Mohit, Behzad (1971)
13 clonal cell lines were isolated from a hybrid cell population established by cell fusion between cloned BALB/c myeloma cells that were resistant to 8-azaguanine and produced immunoglobulin G and free kappa chain and C(67)BL/6n lymphoma cells that were resistant to bromodeoxyuridine and did not produce immunoglobulins. Some of the histocompatibility-2 antigens of both parental cell lines could be demonstrated on all of the hybrid clones. 11 clones synthesized only free kappa chain. Two clones synthesized IgG of BALB/c type, as well as free kappa chain. These clones had higher chromosome number than did the clones that synthesized only kappa chains.